Liver abscess caused by Clostridium haemolyticum infection after transarterial chemoembolization for hepatocellular carcinoma: A case report. Issue 19 (May 2018) - Son, Dong-Jun; Hong, Ji-Yun; Kim, Ki-Hyun; Jeong, Young-Hoon; Myung, Dae-Seong; Cho, Sung-Bum; Lee, Wan-Sik; Kang, Yang-Jun; Kim, Jin-Woong; Joo, Young-Eun
Abstract: Rationale: Liver abscesses caused by Clostridium species infection are extremely rare. Patient concerns: The authors report the first case of a liver abscess due to Clostridium haemolyticum, which occurred after transarterial chemoembolization (TACE) for hepatocellular carcinoma, in a 76-year-old woman who presented with right upper quadrant pain and fever. Diagnoses: Computed tomography of the abdomen after the second TACE showed an air-filled abscess around a compact, lipiodolized lesion in the right hepatic lobe. Pus culture showed the growth of C haemolyticum . Interventions: Broad-spectrum antibiotics, including piperacillin/tazobactam and metronidazole, were administered, and a percutaneous 10-French pigtail catheter for pus drainage and culture was inserted in the liver abscess. Outcomes: Despite administering intensive treatments, she presented with rapid deterioration in mental status, liver function, and infection markers. She was transferred to the local hospital for palliative conservative treatment. Lessons: Clostridia infections, including those involving C haemolyticum, are extremely rare, but should be considered as one of the causative organisms of liver abscess formation after TACE because of its rapid and fatal clinical course.